Smoothly Transitive Fixed Frequency Hysteresis Current Control Based on Optimal Voltage Space Vector - Jiang Zeng; Lin Yang; Yuchang Ling; Haoping Chen; Zhonglong Huang; Tao Yu; Bo Yang (Energies, 2018)
This paper proposes a smoothly transitive fixed frequency hysteresis current control (ST-FHCC) scheme applied to an active power filter (APF). First of all, a switching fixed frequency hysteresis current control (S-FHCC) is introduced, which is based on phase-to-phase decoupling and switching the control strategies under mode 0 or mode 1, and its weakness is described in detail. To enhance it, an improved approach of regulating the hysteresis bandwidth is presented to fix the switching frequency with switch phases being regulated, based on the optimal voltage space vector (OVSV). Furthermore, a flexible division of the voltage-space-vectors diagram is developed to divide the original voltage-space-vectors diagram into six sub-regions, upon which the control strategies under mode 0 and mode 1 can be switched alternately in order to obtain a smooth transition. As a consequence, ST-FHCC can thoroughly avoid the inherent weakness of S-FHCC of switching that is not smooth as a result of the low control accuracy of current errors. Case studies are carried out through power systems computer aided design/electromagnetic transients including DC (PSCAD/EMTDC) while simulation results verify the effectiveness and superiority of ST-FHCC compared to S-FHCC.